2018
DOI: 10.3390/cli6010003
|View full text |Cite
|
Sign up to set email alerts
|

The Antarctic Centennial Oscillation: A Natural Paleoclimate Cycle in the Southern Hemisphere That Influences Global Temperature

Abstract: Abstract:We report a previously-unexplored natural temperature cycle recorded in ice cores from Antarctica-the Antarctic Centennial Oscillation (ACO)-that has oscillated for at least the last 226 millennia. Here we document the properties of the ACO and provide an initial assessment of its role in global climate. We analyzed open-source databases of stable isotopes of oxygen and hydrogen as proxies for paleo-temperatures. We find that centennial-scale spectral peaks from temperature-proxy records at Vostok ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(51 citation statements)
references
References 88 publications
6
45
0
Order By: Relevance
“…The findings of the present study could be attributed to the regional-scale imprints of the large-scale global warming hiatus (GWH) that is referred to as the global warming slowdown, on a period of relatively small warming in the surface temperature of the Earth [12,13]. Additionally, it is suggested that the Antarctic Oscillation (AAO), also known as the Southern Annular Mode (SAM), which is a low-frequency mode of atmospheric variability of the Southern Hemisphere, can affect not only the climate change in the Southern Hemisphere but also in the Northern Hemisphere [49][50][51]. The AAO is capable of influencing the AO through remotely connected atmospheric variability.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study could be attributed to the regional-scale imprints of the large-scale global warming hiatus (GWH) that is referred to as the global warming slowdown, on a period of relatively small warming in the surface temperature of the Earth [12,13]. Additionally, it is suggested that the Antarctic Oscillation (AAO), also known as the Southern Annular Mode (SAM), which is a low-frequency mode of atmospheric variability of the Southern Hemisphere, can affect not only the climate change in the Southern Hemisphere but also in the Northern Hemisphere [49][50][51]. The AAO is capable of influencing the AO through remotely connected atmospheric variability.…”
Section: Discussionmentioning
confidence: 99%
“…IPCC AR5 further confirmed that the greenhouse gas emissions from human activities are the major causes of current climate change [2]. Recently, some studies have shown that CO 2 and global temperature may not be coupled as tightly as previously believed, some other physical mechanisms are also possible candidates for causing the contemporary global warming [3], but each country should not reduce the urgency to regulate anthropogenic carbon emissions because of a possible connection between carbon emissions and biodiversity extinction [4].The main sources of anthropogenic carbon emissions are fossil fuels, and of these, coal produces the largest emissions. To achieve the goal of 2 • C temperature control, countries must strengthen actions to reduce greenhouse gas emissions.…”
Section: Introductionmentioning
confidence: 92%
“…Previous investigators have observed that "despite the clear importance of the SAM (i.e., AAO) in the modern/future climate, very little is known regarding its behavior during pre-industrial times" [13] (p. 1). If the ACO and the AAO/SAM are the same natural climate cycle, discovery of the ACO in multiple paleoclimate records over hundreds of millennia before the onset of the Industrial Age ( [11], this paper) promises to provide the missing historical record of the AAO. In this case, understanding the ACO is expected to illuminate the AAO, and conversely.…”
Section: Introductionmentioning
confidence: 98%
“…Forces external to the Earth, such as periodic variation in solar insolation at the surface induced by natural perturbations of Earth's orbital cycles, drive at least some of these natural climate cycles [3], but in no case are the Earth's internal responses to such external forcing fully understood. In the present study we investigate one such cycle, the Antarctic Centennial Oscillation (ACO) [11] over the past approximately 21,000 y from the Last Glacial Maximum (LGM) to the present. The primary purpose of our study is to elucidate the internal climate dynamics of the ACO, including its regional distribution, teleconnection, geographic source, and method of generation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation